Percutaneous absorption drugs, cosmetics, mechanisms, methods - Dragićević, Nina; Maibach, Howard I. 1929- (CRC Press, Taylor & Francis Group, 2022)
"Updating and expanding the scope of topics covered in the previous edition, Percutaneous Absorption: Drugs, Cosmetics, Mechanisms, Methods Fifth edition supplies new chapters on topics currently impacting the field including cutaneous metabolism, skin contamination, exposure to protein allergens, in vitro absorption methodology and the percutaneous absorption of chemical mixtures. Complete with studies on the role of the skin as a key portal of entry for chemicals into the body this book serves as a detailed reference source for recent advances in the field, as well as an experimental guide for laboratory personnel"--
Includes bibliographical references and index
2108
Keywords: Kutane Applikation; Transdermales therapeutisches System; Wirkstofffreisetzung; Hautresorption; Transdermal medication; Skin absorption; Skin / Permeability